A modified protocol merging two published techniques for computer guided zygomatic implants surgery: a technical note - Omar Effat Mokhtar Abouzeid; Ramy M. Gaber; Haitham A. Maergy; Hossam El-Dien Hany; Karim M. Abdelmohsen; Marwa A. Elkassaby; Moustafa M. Taha (BMC Oral Health)
Abstract Objectives Zygomatic implant surgery can be difficult due to the limited intraoperative visibility of the surgical field and the complex anatomy of the zygomatic bone, which could lead to serious complications. This study aims to assess the accuracy of zygomatic implants placement using computer-guided surgical templates. Materials and methods A total of 13 zygomatic implants were placed in four participants. Double-sleeve drill guides were used with the help of computer-guided surgical templates designed with a lateral window. The accuracy was evaluated by measuring the linear deviations regarding the implants’ platforms and apices’ positions in addition to the angular deviations. Moreover, deviations of both implants from three fixed planes of space were measured. Results The mean linear deviation at platforms was 2.44 mm ± 1.57 and at the apices 2.32 mm ± 1 while the mean angular deviation was 3.6˚ ± 1.92. Differences at the entry points were 0.43 ± 1.79 mm, 0.39 ± 1.12 mm, and − 0.54 ± 2.00 mm from the mid-sagittal, horizontal, and coronal planes respectively. Differences at the exit points were − 0.75 ± 1.25 mm, -0.06 ± 1.09 mm, and 0.63 ± 1.24 mm from the same planes respectively. Within all planes, there was no statistically significant difference. Conclusion Given the limitations of this study, the use of the computer-guided surgical templates augmented by the double sleeve drill guides allowed favorable control over the tip of the long surgical drill away from vital structures during the zygomatic implant osteotomy. It also allowed control over alveolar crest osteotomy and its placement in a favorable prosthetic position. Overall, this protocol should be considered for further research and improvement to allow more predictable surgical outcomes while preventing the occurrence of complications. Before conducting this study, the protocol was reviewed and approved by the Research Ethical Committee of Faculty of Dentistry, Ain Shams University in meeting no. (105), on 15th of July 2020 with the application no.: (FDASU-RecD072029).